2015
DOI: 10.1111/jam.12887
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of viable but nonculturable Salmonella spp. and Shigella spp. during sludge anaerobic digestion and their reactivation during cake storage

Abstract: Thermophilic anaerobic digestion mainly induced Salmonella spp. and Shigella spp. into VBNC state rather than killed them, suggesting that the biological safety of sewage sludge by temperature-phased anaerobic digestion should be carefully assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…19,20 It is also well-established that anaerobic digester treatment can suppress human pathogen population The algae strain was only added to one set of bioreactors but all bioreactors under this heading were part of the same batch sizes, 21,22 however, recent literature suggests that many pathogens enter a viable but non-culturable state during digestion. 23 Thus, it would be important to implement a pathogen monitoring program for wastewater treated by anaerobic digestion followed by algae cultivation. This is particularly relevant if the water will be re-used in agricultural settings.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 It is also well-established that anaerobic digester treatment can suppress human pathogen population The algae strain was only added to one set of bioreactors but all bioreactors under this heading were part of the same batch sizes, 21,22 however, recent literature suggests that many pathogens enter a viable but non-culturable state during digestion. 23 Thus, it would be important to implement a pathogen monitoring program for wastewater treated by anaerobic digestion followed by algae cultivation. This is particularly relevant if the water will be re-used in agricultural settings.…”
Section: Discussionmentioning
confidence: 99%
“…In environmental conditions, bacteria are submitted to various stresses and lose their culturability, what has been called a Viable but Non-culturable (VBNC) state ( Oliver, 2010 ; Li et al, 2014 ). To circumvent their loss of culturability, several authors have used DNA-based quantification (qPCR) to study bacteria in environmental samples such as soil, wastewater, sludge, manure or compost ( Wéry et al, 2008 ; Klein et al, 2011 ; Fu et al, 2015 ). One of the main criticisms of the use of qPCR for quantifying live bacteria in environmental samples is that it may overestimate the concentration of viable bacteria since extracellular DNA or DNA from non-viable cells can also produce a PCR signal ( Nocker and Camper, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have demonstrated that pathogens can enter into a Viable but Non-Culturable (VBNC) state in biosolids or animal by-products after various treatments, including the AD process ( Higgins et al, 2007 ; Qi et al, 2008 ; Viau and Peccia, 2009 ; Fu et al, 2014 ; Desneux et al, 2016 ). Fu et al (2015) demonstrated the induction of a VBNC state of Salmonella sp. and Shigella sp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations